Federalism, power sharing and the 2011 presidential election in Nigeria (2012)
Power sharing has become a prominent feature of post-election conflict management practice in Africa in recent times. A study of the Nigerian experience provides useful lessons about the theory and practice of power sharing in a divided society with a federal system. Nigeria instituted the ‘zoning with rotation’ principle to shore up the affirmative action/federal character principle earlier devised to manage the inter-ethnic tensions that followed the crisis thrown up by the annulment of the presidential elections of 12 June 1993. This article examines the challenges and debates over power sharing in the build-up to the 2011 elections as a result of the entrance of Goodluck Jonathan (a southerner) into the presidential race, made possible by the death of President Umar Musa Yar’Adua (a northerner) in a clear upset of the power-sharing arrangement. It argues that while the ‘zoning with rotation’ principle remains useful for stability and representation in Nigeria its sustenance depends on its flexible application and the creativity of the elites as they negotiate and manage the power disequilibrium that results from perceived access or lack of access of segments of Nigerian society to top political office. The Nigerian case shows that the ‘zoning with rotation’ principle is problematic as a long-term solution because it constrains the notion of free political competition and the uncertain outcomes that are central to democracy.